Role of IKKα in skin squamous cell carcinomas. (January 2011) - Park, Eunmi; Liu, Bigang; Xia, Xiaojun; Zhu, Feng; Jami, Willette-Brown; Hu, Yinling
Squamous cell carcinoma (SCC) and basal cell carcinoma (BCC) are two major types of skin cancer derived from keratinocytes. SCC is a more aggressive type of cancer than BCC in humans. One significant difference between SCC and BCC is that SCC development is generally associated with cell dedifferentiation and morphological changes. When SCC is converted to spindle cell carcinoma, the latest stage of cancer, the tumor cells change to a fibroblastic cell morphology (epithelial-to-mesenchymal transition) and lose their differentiation markers. Recently, several laboratories have reported altered IκB kinase α (IKKα) protein localization, downregulated IKKα, and IKKα gene deletions and mutations in human SCCs of the skin, lung, esophagus, and neck and head. In addition, IKKα reduction promotes chemical carcinogen- and ultraviolet B-induced skin carcinogenesis, and IKKα deletion in keratinocytes causes spontaneous skin SCCs, but not BCCs, in mice. Thus, IKKα emerges as a bona fide skin tumor suppressor. In this article, we will discuss the role of IKKα in skin SCC development.